Relationship between secondhand electronic cigarette aerosol exposure and mental health problems in adolescents - Ying LI; Furong BAI; Wenwen WANG; Liangpeng WU; Zhouling MENG; Sihui PENG (Zhongguo gonggong weisheng, 2025)
ObjectiveTo investigate the relationship between secondhand e-cigarette aerosol exposure and mental health problems in adolescents, and to provide a reference for the formulation of smoke-free environment policies. MethodsFrom March to June 2023, a multi-stage stratified cluster sampling method was used to conduct an online questionnaire survey of 2 112 full-time students aged ≤18 years nationwide. A χ2 test was used for univariate analysis of demographic information and mental health problems. Binary logistic regression was used to analyze the relationship between secondhand e-cigarette aerosol exposure and mental health problems in adolescents. Multiple linear regression was used to analyze the relationship between secondhand e-cigarette aerosol exposure and the three dimensions of mental health problems in adolescents: somatic symptoms, anxiety/worry, and family relationships. ResultsIn this study the prevalence of mental health problems were 12.03% (254 adolescents) and 620 (29.36%) were exposed to secondhand e-cigarette aerosol. Binary logistic regression analysis showed that adolescents exposed to secondhand e-cigarette aerosol had a 1.500 times higher risk of developing mental health problems than those not exposed (OR = 1.500, 95%CI: 1.127 - 1.998). Multiple linear regression results showed that adolescents exposed to secondhand e-cigarette aerosol in the past 30 days had more severe somatic symptoms (b = 0.758, P < 0.001) and higher anxiety/worry (b = 0.691, P< 0.001). ConclusionsSecondhand e-cigarette aerosol exposure in adolescents is positively correlated with the occurrence of mental health problems, and is related to the dimensions of somatic symptoms and anxiety/worry.